Voltage Improvement on the Feeder Using the Load Breaking Method - Muhammad Fahmi Hakim; Masramdhani Saputra; Rhezal Agung Ananto; Priya Surya Harijanto; Asfari Hariz Santoso (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2023)
Based on observations made by PT. PLN (Persero), Plumpang Feeder has a large voltage drop and high-power loss. To analyze in more detail, a simulation was carried out using ETAP (Electrical Transient Analysis Program) software. The results of the ETAP simulation, the Plumpang Feeder has end voltage of 19,083 V from a nominal voltage of 20,000 V. The voltage drop is -4.58% and the power loss is 594.7 kW or -1122kVAR. To overcome this problem, a load split or breaking method is carried out by moving some of the load of the Plumpang Feeder to the New Plumpang Feeder so that the total load current of the Plumpang Feeder will decrease and the voltage drop and power loss will also decrease. The Load Breaking Method is carried out at each Cut Off (CO) Branch where the loads to be moved. After the Load Breaking Method is applied, based on ETAP simulation results, the end voltage at Plumpang Feeder increased from 19.083 V to 19.307 V or have a change in voltage drop from -4.58% to -3.47%. The power loss decreased from 594.7kW to 92.4kW or experienced a change in power loss from 0.0129% to 0.0043%.